BANI ALAWIYYIN IN INDONESIA AND THE MALAY WORLD: Network, Development and the Role of Institution in Transmitting the Peaceful Mission of Islam (State Islamic University (UIN) of Sunan Ampel Surabaya, 2019)
Bani Alawiyyin is Arabian Muslims community scattering around the world. Their diaspora is due to many factors and motivations: religion (mission), economy, politic, culture, and so on. They are well-known as a community who hold tenacious principle in disseminating Islamic teaching based on the principle of rahmatan lil ‘ālamīn (blessing to universe). This article endeavors to cast light upon social-religious activities that have been practiced by Bani Alawiyyin prioritizing the courtesy aspects of all mankind. This article is also aiming at presenting data findings which can explain that Bani Alawiyyin had truly proselytized non-radical mission among people in Southeast Asia: Indonesia, Singapore, and Malaysia. This article also elucidates the role of Bani Alawiyyin especially in the form of institutional organization in transmitting Islamic doctrine in a peaceful mission. The finding shows that many organization are used by Bani Alawiyyin to spread Islamic teaching in different countries that lead to the success of their mission by determining local and indigenous factors.